Researching indigenous knowledge (IK) in higher education in Zimbabwe: prospects and challenges. - Muyambo, T.; Bhuda, M. T.; Sithole, P. M. (South African Journal of Higher Education, 2025)
Indigenous Knowledge (IK) discourses are confronted by several challenges ranging from methodological, attitudinal, political and financial in nature, yet IK’s agency in 21st century Africa and beyond cannot be doubted. In this article, we show that although a small number of academics are actively engaging in Indigenous Knowledge (IK) research, there remains limited support from other stakeholders along the IK value chain. The data were gathered through in-depth interviews with IK scholars, a review of relevant literature, and informal discussions with colleagues. The data was collated into a narrative and content analysis was used to analyse it. This article made the thesis that a handful of academia in Zimbabwe is doing commendable research on IK but the missing link is that their efforts are not complemented by stakeholders for communities to sustainably benefit from research. There must be “ringed funding” towards IK and a seamless chain of flow of research output from the researchers to the policy makers, implementors and the public as the end users of that information. The connecting cogs in this value chain are conspicuously not connecting.